2015
DOI: 10.1038/srep08278
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Sequencing in Chromosome 17q Linkage Region Identifies Familial Glioma Candidates in the Gliogene Consortium

Abstract: Glioma is a rare, but highly fatal, cancer that accounts for the majority of malignant primary brain tumors. Inherited predisposition to glioma has been consistently observed within non-syndromic families. Our previous studies, which involved non-parametric and parametric linkage analyses, both yielded significant linkage peaks on chromosome 17q. Here, we use data from next generation and Sanger sequencing to identify familial glioma candidate genes and variants on chromosome 17q for further investigation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 56 publications
0
17
1
Order By: Relevance
“…In our experiments, we did not find any changes in expression of MYO19 in prostate cancer cell lines [5]. However, a recent report of a linkage analysis for part of chromosome 17 identified MYO19 as a possible candidate for Glioma, with 2 missense mutations identified [105]. However, the chromosome positions reported currently appear to map to an upstream lincRNA and not to the MYO19 gene.…”
Section: Class 5 6 10 and 19 Myosin Isoformscontrasting
confidence: 44%
“…In our experiments, we did not find any changes in expression of MYO19 in prostate cancer cell lines [5]. However, a recent report of a linkage analysis for part of chromosome 17 identified MYO19 as a possible candidate for Glioma, with 2 missense mutations identified [105]. However, the chromosome positions reported currently appear to map to an upstream lincRNA and not to the MYO19 gene.…”
Section: Class 5 6 10 and 19 Myosin Isoformscontrasting
confidence: 44%
“…Myo19 has recently been implicated in gliomagenesis (Jalali et al, 2015). Moreover, mitochondria were found in filopodia of glioblastoma cells that actively penetrate extracellular matrix (Arismendi-Morillo et al, 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, KIF18B is involved in the separation of chromosomes in mitosis and organizing astral MTs (Kim, Fonseca, & Stumpff, 2014). In recent years, studies have demonstrated that KIF18B was involved in the growth and development of multiple cancers (Jalali et al, 2015;Wu et al, 2018). KIF18B is highly expressed in cervical cancer tissue and further promotes the proliferation and migration of cervical cancer cells (Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%